Fringing effect on the measurement of permittivity of dielectric materials - Chen, Yi Quan. (2010)
In high voltage transmission applications, the measurement of permittivity of dielectric materials is very important, especially during the detection of failure in the insulation. For dielectric materials with high permittivity, fringing effect is negligible because the scattered energy in the ambient is insignificant compared to the predominant energy within the dielectric materials. However, for materials having very low relative permittivity, the measured permittivity of materials significantly differs from its intrinsic value due to fringing effect. For the first part of this report, a computer simulation software, Ansoft Maxwell 2D, is utilized to examine the fringing effect on a pair of parallel-electrodes. The effect of electric field between the plates is also determined. The energy within the dielectric material is computed and compared with the sum of energy within the dielectric material and its surrounding ambient to study its relationship. With the required data, a new value of permittivity resulting from fringing effect can be obtained from the assumed intrinsic permittivity. Set to improve the accuracy of the simulation, the second part of this report used Ansoft Maxwell 3D to carry out the experiment as done in the first part. With the increase in dimension and functional abilities, the results are obtained with a higher level of precision and a more illustrative representation. The last part of the report seeks to apply the theory into a cascaded transformer, a high voltage application. Different sets of values of intrinsic and measured permittivity are assigned to the dielectric material of the cascaded transformer, and the difference between the resulting electric fields is examined.